2012
DOI: 10.1071/an11251
|View full text |Cite
|
Sign up to set email alerts
|

Foraging strategies of goats in a pasture of wheat and shrubland

Abstract: Cereal pastures are a crucial source of forage to reduce grazing pressure on shrublands in the Mediterranean basin. This study aimed at investigating the grazing preferences and behaviours of goats with different genotypes, when a grazing area of shrubland (0.18 ha), which was composed of 88% shrubs, 10% herbaceous species and 2% footpath and wheat (Triticum aestivum L.) pasture (0.20 ha) were offered together. Twelve lactating mature (in 2007) and 15 non-lactating yearling goats (in 2008) of three genotypes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
1
9
0
2
Order By: Relevance
“…In an extensive West African system, goats could browse to an equivalent height as cattle (1 m), and Sanon et al (2007) reported goats browsing up to a height of 2.1 m. In a small Brazilian study, Pfister et al (1988) found that goats spent up to 8% of their time feeding on their rear legs despite ample availability of lower level forage. Interestingly, in a Turkish extensive shrubland, there were breed differences, with Turkish Saanens bipedal standing at least twice as much as the other breeds ( Tölü et al, 2012 ).…”
Section: Natural Behavior Of Goatsmentioning
confidence: 98%
“…In an extensive West African system, goats could browse to an equivalent height as cattle (1 m), and Sanon et al (2007) reported goats browsing up to a height of 2.1 m. In a small Brazilian study, Pfister et al (1988) found that goats spent up to 8% of their time feeding on their rear legs despite ample availability of lower level forage. Interestingly, in a Turkish extensive shrubland, there were breed differences, with Turkish Saanens bipedal standing at least twice as much as the other breeds ( Tölü et al, 2012 ).…”
Section: Natural Behavior Of Goatsmentioning
confidence: 98%
“…Thus it can be stated that Gökçeada sheep walked more during the resting periods through travelling between the paddocks and rangeland compared with the grazing periods. In a study carried out on goats of different breeds and ages, Tölü et al (2012) determined with 8 h of daily observation that goats demonstrated walking behaviour 18•5-51•7 times daily per animal and also determined that Gökçeada goats walked the least. Slightly lower walking frequencies in the present study were because the sheep were continuously free to go to the rangeland.…”
Section: Discussionmentioning
confidence: 99%
“…Odds ratio was defined here as the ratio of observation to non-observation of behaviour. This ratio was calculated from the equation ψ = e b , where ψ is the odds ratio, b is the regression coefficient, and 'e' is the exponential constant (Yurtman et al 2002;Tölü et al 2012). The post-hoc analyses were made according to Wald χ 2 test.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Dry matter contents of feed samples were determined in accordance with the methods specified in AOAC (1990) and carbohydrate analyses were carried out in accordance with the methods specified in ANKOM (2005) . Nitrogen (N) content was determined in a Carbon-Nitrogen Auto Analyzer (LECO TruSpec CN, St Joseph, MI, USA) and then crude protein content was determined using the formula of CP = N×6.25 ( Tölü et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%